Bisphosphonates Targeting Ion Channels and Musculoskeletal Effects - Scala, Rosa; Maqoud, Fatima; Antonacci, Marina; Dibenedetto, Jacopo Raffaele; Perrone, Maria Grazia; Scilimati, Antonio; Castillo, Karen; Latorre, Ramón; Conte, Diana; Bendahhou, Saïd; Tricarico, Domenico (Frontiers in Pharmacology, 2022)
Bisphosphonates (BPs) are the most used bone-specific anti-resorptive agents, often chosen as first-line therapy in several bone diseases characterized by an imbalance between osteoblast-mediated bone production and osteoclast-mediated bone resorption. BPs target the farnesyl pyrophosphate synthase (FPPS) in osteoclasts, reducing bone resorption. Lately, there has been an increasing interest in BPs direct pro-survival/pro-mineralizing properties in osteoblasts and their pain-relieving effects. Even so, molecular targets involved in these effects appear now largely elusive. Ion channels are emerging players in bone homeostasis. Nevertheless, the effects of BPs on these proteins have been poorly described. Here we reviewed the actions of BPs on ion channels in musculoskeletal cells. In particular, the TRPV1 channel is essential for osteoblastogenesis. Since it is involved in bone pain sensation, TRPV1 is a possible alternative target of BPs. Ion channels are emerging targets and anti-target for bisphosphonates. Zoledronic acid can be the first selective musculoskeletal and vascular KATP channel blocker targeting with high affinity the inward rectifier channels Kir6.1-SUR2B and Kir6.2-SUR2A. The action of this drug against the overactive mutants of KCNJ9-ABCC9 genes observed in the Cantu’ Syndrome (CS) may improve the appropriate prescription in those CS patients affected by musculoskeletal disorders such as bone fracture and bone frailty.